Biophysical study regarding the effect of hydrogen sulfide on molecular structure and DNA of mammalian cornea - E. Ibrahim, Amal; M. Awad, Sahar; M.Elshibly, Shimaa; M kamal, Gehan (International Journal of Engineering and Technology, 2018)
Background: Humans are affected by both exogenous and endogenous sources of hydrogen sulphide gas (H2S). Its health effects depend on concentration and the duration of gas exposure. These hazards include-among many effects-eye irritation, tearing and inflammation.Objectives: Our study aimed to characterize the side effects induced in cornea due to H2S exposure by using by means of comet assay and Fourior Transformer Infrared Radiation (FTIR).Materials and methods: sixty chinchilla rabbits were randomly grouped into four groups. Group one served as control. Animals were exposed to hydrogen sulphide gas with concentrations of, 90, 250 and 500 ppm. After exposure, animals were decapitated, and the eyes were enucleated from the eye globe. Their corneas were obtained by sectioning through ora serrate. Corneas were then kept frozen at â€“ 20Â° C for analysis by FTIR spectral and comet assay analysisResults: NH-OH region changes revealed unusual interface/binding mechanism that related to different surrounding environment as well as co-existence of different formations and conformations in the system after exposure to H2S gas. Moreover the exposure to H2S gas has no effect on the CH stretching region that arising from lipid. All parameters of comet assay significantly increase (pË‚0.05) due to exposed doses. This increase is directly proportional to the increase in exposure level.Conclusion: Hydrogen sulfide is a very toxic gas to cornea which is considered as window of the eye .it has a serious effect on molecular structure and DNA of cornea. By better understanding its toxicity, we will be able to safely make use of its various benefits without the threat of harm looming over our heads.Â